Etnoekologi Highland Wild Dog (Canis hallstromi, Troughton 1957) Berdasarkan Pengetahuan Masyarakat Lokal di Puncak Jaya, Papua - Leonardo A. Numberi; Suriani Br. Surbakti; Henderina J. Keiluhu (Jurnal Biologi Papua, 2022)
Highland Wild Dog (HWD) is Canis hallstromi from Papua that was distributed in Puncak Jaya area and is close to tribal Amungme, Damal, and Moni Kamoro. The aim of the study is to find out the local knowledge of Amungme, Damal, Moni, and Kamoro tribes about the population and behavior of HWD. The research began on the interview, then continued to obeservation using 11 camera traps placed in Gresberg area in Puncak Jaya. Analysis used is interval level values, while for measuring the HWD density and behavioral we used documentation technic. Results of the interview provide various information from each tribe related to morphology, behavior, role, management, and mythology of HWD. Result of this study reveals that the Amungme and Moni tribes have a concept in the preservation of HWD. It could be seen from the habit of people who do not utilised the HWD for hunting. Instead, they prepare a place for nursery even a den for the dogs. All the  informations collected from the community is also scientifically proven that HWD is C. hallstromi distributed in Papua, especially subalpine and alpine in Puncak Jaya, estimated population of HWD is ± 200 individuals. Observed behavior of these dogs are howling, rolling, rubbing, and having communal toilet spots. Generally, they have social behavior in groups with the number of 3-5 individuals and usually one of them is a male dog. Key words: Canis hallstromi;Ecology; Ethnoecology; Puncak Jaya.